Coregistration of eye movements and EEG reveals frequency effects of words and their constituent characters in natural silent Chinese reading - Taishen Zeng; Longxia Lou; Zhi-Fang Liu; Chaoyang Chen; Zhijun Zhang (Scientific Reports)
Abstract We conducted two experiments to examine the lexical and sub-lexical processing of Chinese two-character words in reading. We used a co-registration electroencephalogram (EEG) for the first fixation on target words. In Experiment 1, whole-word occurrence frequency and initial constituent character frequency were orthogonally manipulated, while in Experiment 2, whole-word occurrence frequency and end constituent character frequency were orthogonally manipulated. Results showed that word frequency facilitated eye-tracking measures, while initial and end character frequencies inhibited them. Classical word frequency effects on N170 and N400 in the posterior region and reversed word frequency effects over the anterior region were consistently observed in both experiments. Experiment 1 revealed an inhibiting effect of initial character frequency on anterior N170. In Experiment 2, interaction between end-character frequency and word frequency showed reliable effects on anterior N170 and N400. These results demonstrate both facilitating and inhibiting word frequency effects, along with inhibiting effects of character frequency and that word frequency moderates the inhibiting effects of end constituent character frequency during natural silent Chinese reading.